Factors influencing user acceptance of virtual reality in preserving Wuhu iron painting from the unified theory of acceptance and use of technology perspective - Yuting Zhu; Xin He (Scientific Reports)
Abstract This study explores the potential of virtual reality (VR) in preserving intangible cultural heritage (ICH), focusing on Wuhu iron painting. We developed and applied a VR system that simulates the process of creating Wuhu iron paintings, which was introduced to participants during an experimental session. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) model, a survey was conducted with 668 participants to analyze the influence of performance expectancy (PE), effort expectancy (EE), social influence (SI), and facilitating conditions (FC) on VR adoption. The findings reveal that PE and SI significantly influence users’ intention to adopt VR for Wuhu iron painting, highlighting the importance of perceived benefits and community endorsement. In contrast, EE and FC had a minimal impact, suggesting that prior exposure to VR reduces concerns about usability. These insights underscore the importance of developing targeted engagement strategies, ensuring that VR applications are designed with user expectations and cultural context in mind.